Analysis of occupational stress, burnout, and job satisfaction among dental practitioners - Anzar, Wajiha; Qureshi, Ambrina; Afaq, Ashar; Alkahtany, Mazen F; Almadi, Khalid H; Ben Gassem, Afnan A; AlRefeai, Mohammad H; Naseem, Mustafa; Vohra, Fahim; Abduljabbar, Tariq (Work (Reading, Mass.), 2022)
Dental practitioners can be prone to stress because of the long working hours, high patient expectations, and work environment. To investigate dimensions of occupational stress among dental practitioners leading to burnout and to model its causality with job satisfaction. An analytical cross-sectional study was conducted for five months. A sample of 302 practicing dental practitioners was selected using the consecutive sample technique. This sample included dental practitioners working in clinical and non-clinical departments of public and private sector universities as well as those doing private general practice. A self-administered structured questionnaire based on the Work Stress Questionnaire was sent using Survey Monkey. Descriptive statistics were calculated. Spearman correlation was applied between stress scores and job satisfaction. A Chi-square test was applied to look into the association between stress levels and different categories. Univariate and multivariate analysis was performed. The prevalence of overall occupational stress was high among dental practitioners (83.4%). Occupational stress was greatest in females (55.8%), dental practitioners in the private sector (55.7%), and general dental practitioners (GDPs) (47%). The overall prevalence of job satisfaction among dental professionals was 30%. Occupational stress was significantly associated with burnout and job dissatisfaction in dentistry. Stress levels and working hours were statistically and positively associated, whereas the association between stress levels and job satisfaction was inversely and significantly associated. The prevalence of occupational stress among dental practitioners was high and the level of job satisfaction was moderate. The model between these variables was well-fitted.